Hybrid Coding Technique for Pulse Detection in an Optical Time Domain Reflectometer - Muhammad, S. Sheikh; Mehmood, Haleema; Naseem, Anwar; Abbas, Aun (Společnost pro radioelektronické inženýrství, 2012)
The paper introduces a novel hybrid coding technique for improved pulse detection in an optical time domain reflectometer. The hybrid schemes combines Simplex codes with signal averaging to articulate a very sophisticated coding technique that considerably reduces the processing time to extract specified coding gains in comparison to the existing techniques. The paper quantifies the coding gain of the hybrid scheme mathematically and provide simulative results in direct agreement with the theoretical performance. Furthermore, the hybrid scheme has been tested on our self-developed OTDR.
Keywords: Optical Time Domain Reflectometer (OTDR); signal averaging; Golay codes; Simplex codes; pulse detection; composite coding scheme